Remission Policy for Corruption Convicts under Law Number 22 of 2022 on Corrections - Syahrial Yuska; Alfarizeki Edytiawarman (UIN Fatmawati Sukarno Bengkulu, 2026)
The implementation of remission policy for corruption convicts under Law Number 22 of 2022 on Corrections presents a complex challenge within Indonesia’s legal system. Remission in extraordinary crimes like corruption should not be seen merely as an administrative right but must be analyzed through the lens of substantive justice, social accountability, and restitution of state losses. Using a normative-empirical qualitative approach, through legal analysis, literature review, and interviews with criminal law scholars and practitioners. This study finds that remission remains largely uniform and administrative, lacking consideration of key substantive criteria such as asset recovery or social risk assessment. The absence of a Government Regulation as a technical derivative of the law further exacerbates inconsistency in implementation across institutions. From a public policy perspective, this illustrates a significant implementation gap, while from Thomas Aquinas’s theory of legal justice, the policy falls short of achieving general justice and the bonum commune. Reform is thus needed, including the application of proportionality principles, classification of offenses, substantive evaluation indicators, and the engagement of multi-agency actors. Integrating public policy with philosophical justice theory affirms that remission should function as part of a legal rehabilitation mechanism—respecting inmates’ rights while fulfilling public justice and moral responsibility. Such reforms are vital for restoring the legitimacy of Indonesia’s correctional system and advancing comprehensive anti-corruption efforts.